Lean healthcare: a cross-section of South African ARV clinics - Chatur, Sabrina (My University, 2018)
The aim of this study is to assess waste in Anti-Retroviral (ARV) Clinics. This is against the background of an overburdened public sector – that serves a large percentage of the population in South Africa. South Africa is home to the to the world’s largest epidemic with approximately 7,06 million - 18.0% of general population, living with HIV as of 2017 (1). The objective of the study is to identify and categorise the drivers of waste present ARV Clinics - to evaluate the resultant impact of waste on the governance and administration of ARV Clinic operations as well as service delivery to the patient. Frameworks have been developed to measure and assess waste – with the hope that they will pave a pathway for the introduction of lean in ARV Clinics and in time the public health system. To achieve this, the research employs a qualitative analysis design approach incorporating both primary sources (multiple case studies) and secondary sources (academic publications and grey literature) of data. The study found that there is an abundance of waste in the daily operations of the ARV Clinics – there are very few people in the clinics and hospitals who ‘see’ these wastes because there is a need to develop the capabilities of the staff, as they are the essential foundation for improving partnerships, processes and the provision of service. However, the waste did not only exist at operational levels – the biggest potential for elimination of waste laid at the top, with the National Department of Health (NDoH), where policies and budgets are rolled out that affect what happens to the ARV clinics – a holistic approach to transformation needs to be considered. The research provides a contribution to knowledge in three key areas: firstly, through the development of frameworks, secondly through the validation of the frameworks via multiple case studies; and thirdly suggestions that provide a narrative that explain the link between waste - overall performance of ARV Clinics and the quality of service to patients.
A research Report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science in Engineering Date: 28th May 2018
Keywords: Medical care--South Africa; Public health--South Africa; AIDS (Disease)--Social aspects--South Africa